پاکستان کے مشترکہ خاندانی نظام میں رہائش سے متعلقہ مسائل اور ان کا حل (اسلامی تعلیمات کی روشنی میں ایک جائزہ): Issues of Accommodation in the joint family system of Pakistan and their solution (An analytical study in the context of the Islamic teachings) - Rafiq, Dr. Shabana; Rafiq, Saad; Akhtar, Dr. Tanveer (Al-Amīr Research Journal for Islamic Studies, 2023)
A family is the fundamental unit of society. Every society has the presence of a family. The start of a family’s life is entirely dependent on matters of co. human relations. All such human relationships are entrenched in islamic sharia as a sacred bond of nikah, in which a husband and wife become a part of the world in the form of a family’s collective result. Husband and wife are the most fundamental pillars of society, and their affection and companionship provides a source of stability for them and also a refuge for coming generations.A family consist of husband ,wife and their children . The family life is begins with marriage, after marriage every woman wants to have her own separate home where all the requirements of privacy are met. Islam has placed the entire responsibility of livelihood on men..But in our society there are two types of family system joint and separate family system. In Pakistan The joint family system is prevalent. The people of the subcontinent are not only adopting this system but they are also feel proud of it . In the present article the joint family system has facing many challenges. One of them is accommodation. In this article will focus on what is the basic concept of accommodation in joint family systems and its solution in Islami teachings. It is critical for the husband and wife to have a home where no one can interfere on their personal matters. This interference is very much in our society.Which husband and wife facing many problems. And due to this conditions, the relationship of husband and wife is also affected. Key Words: Joint family system, Issues of Accommodation, Pakistani society, Islamic teachings.